Skeletal loading: Lean and bone mass development in young elite male gymnasts, swimmers, and nonathletes aged 6-24 years - Gannon, L.; Hind, K. (Pediatric Exercise Science, 2024)
Background: Exercise optimizes peak bone mass accrual, particularly if the loading is high magnitude and distributed in abnormal directions. Little is known about the influence of early intense training in sport during peak bone mass accrual, especially in boys.